ANALISIS KINERJA INFRASTRUKTUR TRANSPORTASI KABUPATEN MUNA BARAT - Musliady Al Askalany; Achmad Fadly; Reni Salfatir (Pascasarjana Universitas Halu Oleo, 2019)
The policy of providing road infrastructure that is right and effective, requires an instrument that can see the success rate of providing road infrastructure in balancing economic development, population and number of vehicles. The purpose of this study was to analyze the performance of transportation infrastructure in this case the condition of the West Muna Regency road network.This research was conducted in two ways, namely using the Road Infrastructure Index (IPJ) and Minimum Service Standards (SPM). The road infrastructure index uses four variables which are also indicators in the assessment of the availability of road infrastructure (Ktj), road network performance (KNJ), traffic load (BLN) and road infrastructure services (Pyp). While the Minimum ServiceStandards are viewed from the Accessibility Index and Mobility Index.The results of the study showed that the performance of transportation infrastructure based on the 2016 West Muna Regency Road Infrastructure Index (3.78) was said to be insufficient according to the national minimum value (6.00) and national average value (5.68). Based on the Minimum Service Standards of West Muna Regency, accessibility and mobility indices have met the existing requirements. Keywords: Transportation Infrastructure Performance, Road Network System, RoadInfrastructure Index (IPJ), Minimum Service Standards (SPM)